Inflammasomes: a rising star on the horizon of COVID-19 pathophysiology - Wang, Man; Yu, Fei; Chang, Wenguang; Zhang, Yuan; Zhang, Lei; Li, Peifeng (Frontiers in Immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a contagious respiratory virus that is the cause of the coronavirus disease 2019 (COVID-19) pandemic which has posed a serious threat to public health. COVID-19 is characterized by a wide spectrum of clinical manifestations, ranging from asymptomatic infection to mild cold-like symptoms, severe pneumonia or even death. Inflammasomes are supramolecular signaling platforms that assemble in response to danger or microbial signals. Upon activation, inflammasomes mediate innate immune defense by favoring the release of proinflammatory cytokines and triggering pyroptotic cell death. Nevertheless, abnormalities in inflammasome functioning can result in a variety of human diseases such as autoimmune disorders and cancer. A growing body of evidence has showed that SARS-CoV-2 infection can induce inflammasome assembly. Dysregulated inflammasome activation and consequent cytokine burst have been associated with COVID-19 severity, alluding to the implication of inflammasomes in COVID-19 pathophysiology. Accordingly, an improved understanding of inflammasome-mediated inflammatory cascades in COVID-19 is essential to uncover the immunological mechanisms of COVID-19 pathology and identify effective therapeutic approaches for this devastating disease. In this review, we summarize the most recent findings on the interplay between SARS-CoV-2 and inflammasomes and the contribution of activated inflammasomes to COVID-19 progression. We dissect the mechanisms involving the inflammasome machinery in COVID-19 immunopathogenesis. In addition, we provide an overview of inflammasome-targeted therapies or antagonists that have potential clinical utility in COVID-19 treatment.